Corporate Failure Prediction Model of UK Wholesale Industry - Li, Cong (2009)
The target of this research is to develop a corporate failure prediction model for UK wholesales industries with recent ten year data. Different time period and techniques are compared to look for the best model. Non-financial variables are also added to see if they can improve the prediction power. The result shows that discriminant analysis model with change per year of each variables has the best prediction on failed firms. Models from multiple period data are not necessarily better than single period model. And non-financial variables tested are not significant in failure prediction.